Cover Jurnal Media Teknik Sipil Vol.13 No.1, Februari 2015 - ., Cover (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2015)
Cover Jurnal Media Teknik Sipil Vol.13 No.1, Februari 2015